HASIL ANALISIS BELAJAR MEMBACA ANAK PASCA COVID-19 - Bunga Nur Fadillah; Kumala Sari; Michelle Andhi Aprilyne (Universitas Muhammadiyah Surabaya, 2022)
The use of gadgets if used excessively can have a bad effect on users, especially children on their social development. Especially when the covid pandemic which has lasted for almost three years has made many school children carry out online learning activities, and playing on their devices too often has a bad effect. Children become closed individuals, have sleep disorders and irregular lifestyles, become private individuals who like to be alone, have the effect of violence, decrease creativity, and are threatened with bullying. The tendency to use gadgets can make children experience what is called speech delay. The research method used in this study is a qualitative research method. The results showed that most children of concrete operational age when using gadgets too often make them have a high level of concentration on lessons, they are less active in finding solutions when faced with a question. The factors that can affect children's addiction or excessive use of gadgets are the lack of parental supervision and discipline, the feeling that parents are not able to teach children to learn so that parents allow their children to use gadgets.Â Keywords: Gadget, Decreased Creativity, Discipline